Crystallization and X-ray structure of cold-shock protein E from Salmonella typhimurium - Morgan, Hugh P. (International Union of Crystallography, 2009)

(untitled)
In prokaryotic organisms, cold shock triggers the production of a small highly conserved family of cold-shock proteins (CSPs). CSPs have been well studied structurally and functionally in Escherichia coli and Bacillus subtilis, but Salmonella typhimurium CSPs remain relatively uncharacterized. In S. typhimurium, six homologous CSPs have been identified: StCspA–E and StCspH. The crystal structure of cold-shock protein E from S. typhimurium (StCspE) has been determined at 1.1 Å resolution and has an R factor of 0.203 after refinement. The three-dimensional structure is similar to those of previously determined CSPs and is composed of five antiparallel β-strands forming a classic OB fold/five-stranded β-barrel. This first structure of a CSP from S. typhimurium provides new insight into the cold-shock response of this bacterium.